Jimmy Coates: Revenge - Joe Craig (London Harper Collins Children's Books, 2007)
A third action-packed adventure for the incredible Jimmy Coates. Will Jimmy Coates ever be free of NJ7? Why should they need to find him if they are able to control him. Through Christopher Viggo's powerful new contacts, Jimmy and his friends escape to the USA. They go into hiding in Chinatown, New York City. While they are there, Jimmy finds himself experiencing headaches accompanied by flashing images - something that hasn't happened to him before. Are they prophetic visions? Can Jimmy piece together the puzzle of his obsession before time runs out? And how can he convince anybody of what he thinks he knows, when the only evidence is locked inside his head? Revenge will come. But what form will it take?